The Effects of Industrial Soil Pollution on Prosopis juliflora Swartz Growth Around Karachi: Effect of Industrial Soil Pollution on P. juliflora - Rehman, Syed Atiq-ur-; Iqbal, Muhammad Zafar (Biological Sciences - PJSIR, 2009)
. Study of the effect of soils of towel, garment, rubber and ply-wood factories of Korangi and Landhi industrial estates of Karachi and that of the University of Karachi on the growth of Prosopis juliflora Swartz plants growing in these areas demonstrated detrimental effect of industrial soils on the growth of plants of all the areas particularly on the plants growing at the University site.